Weighted Multipath Energy-Aware Clustered Stable Routing Protocol for Mobile Ad Hoc Networks - Mohindra, Anubhuti; Gandhi, Charu (International Journal of Sensors Wireless Communications and Control, 2020)
Background & Objective: Mobile ad hoc networks are defined as highly dynamic, leading to frequent disconnections and changing topologies. The energy and stability of power limited nodes needs to be managed while designing the protocol & clustering helps in reducing the problem of network congestion due to information overhead in large sized networks. Multipath routing helps in balancing the load and node failures in a dynamic environment thereby helping to solve the problem of congestion. This paper proposes a new multipath, energy-aware and stable routing protocol – Weighted Multipath Energy-aware Clustered Stable routing protocol (WMECS). Methods: It uses weighted approach in clustered mobile adhoc networks. In this, both cluster head as well as path selection is done using an optimal energy and mobility model. This helps in attaining stable and energy efficient network with prolonged lifetime. The energy model considers energy metrics like transmission power, drain rate and power load that helps in constructing a network with lower energy consumption. We have also considered Gauss-Markov Mobility Model to handle the mobility of nodes and attain a stable network with less re-clustering and re-affiliations by choosing low relative mobility nodes in every cluster. Multipath selection is done based on a weighted metric that considers energy and mobility coefficients whereas Optimal Paths are selected on the basis of lower weight. Results: Simulation results show that the proposed protocol has better performance when compared with other related protocols in terms of Energy Consumption, Network Lifetime and end to end delay.
Keywords: transmission power control